PERSIAPAN PETUGAS RAMP HANDLING DI BANDARA ABDUL RACHMAN SALEH DALAM PROSES PERSIAPAN PEMBERANGKATAN - Evaf Maulina (JURNAL MITRA MANAJEMEN, 2021)
ABSTRACTThe company's operational activities are indeed the main point in achieving the targets to be achieved. This applies to every airline company that is a direct customer such as a passenger. Ground Handling, namely the pre-flight service and post-flight service phases, namely the handling of passengers and aircraft while at the airport. The ramp handling officer is tasked with carrying out field activities based on existing SOPs. Keyword : Ground Handling, Ramp Handling